Wisconsin sports geography : collegiate football recruiting patterns in the Wisconsin Intercollegiate Athletic Conference 2007-2001. - Boyd, Eugene (My University, 2008)
This research focuses on the geographical relationships and landscapes of high school football recruiting in Wisconsin as it pertains to the college programs that operate in absence of athletic scholarships within the Wisconsin Intercollegiate Athletic Conference.
Wisconsin sports geography : high school football recruiting.
Color poster with text and maps describing research conducted by Eugene Boyd under the supervision of Ingolf Vogeler.
Keywords: College athletes--Recruiting--Wisconsin.; Football players--Wisconsin.; College sports--Regional disparities.; Human geography--Wisconsin.; Wisconsin Intercollegiate Athletic Conference.; Posters.